Resenha de: Zirker, Daniel. "Forging military identity in Culturaly Pluralistic Societies: quasi-ethnicity". Maryland: Lexington Books, 2015 - Mathias, Suzeley Kalil (Revista Brasileira de Estudos de Defesa, 2016)
Resenha do livro organizado por Daniel Zirker: Zirker, Daniel. (2015) Forging military identity in Culturaly Pluralistic Societies: quasi-ethnicity. Maryland: Lexington Books, 133pp. ISBN 978-1-4985-0743-1